The taming of the cell: shape-memory nanopatterns direct cell orientation - Ebara, Mitsuhiro (Dove Medical Press, 2014)
We report here that the direction of aligned cells on nanopatterns can be tuned to a perpendicular direction without use of any biochemical reagents. This was enabled by shape-memory activation of nanopatterns that transition from a memorized temporal pattern to the original permanent pattern by heating. The thermally induced shape-memory nanopatterns were prepared by chemically crosslinking semi-crystalline poly(ε-caprolactone) (PCL) in a mold to show shape-memory effects over its melting temperature (T(m) = 33°C). Permanent surface patterns were first generated by crosslinking the PCL macromonomers in a mold, and temporary surface patterns were then embossed onto the permanent patterns. The temporary surface patterns could be easily triggered to transition quickly to the permanent surface patterns by a 37°C heat treatment, while surface wettability was independent of temperature. To investigate the role of dynamic and reversible surface nanopatterns on cell alignment on the PCL films before and after a topographic transition, NIH 3T3 fibroblasts were seeded on fibronectin-coated PCL films with a temporary grooved topography (grooves with a height of 300 nm and width of 2 μm were spaced 9 μm apart). Interestingly, cells did not change their direction immediately after the surface transition. However, cell alignment was gradually lost with time, and finally cells realigned parallel to the permanent grooves that emerged. The addition of a cytoskeletal inhibitor prevented realignment. These results clearly indicate that cells can sense dynamic changes in the surrounding environments and spontaneously adapt to a new environment by remodeling their cytoskeleton. These findings will serve as the basis for new development of spatiotemporal tunable materials to direct cell fate.